2021
DOI: 10.1021/acs.jpca.1c01295
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Avenues beyond Revised DSD Functionals: II. Random-Phase Approximation and Scaled MP3 Corrections

Abstract: For revDSD double hybrids, the Görling–Levy second-order perturbation theory component is an Achilles’ heel when applied to systems with significant near-degeneracy (“static”) correlation. We have explored its replacement by the direct random phase approximation (dRPA), inspired by the SCS-dRPA75 functional of Kállay and co-workers. The addition to the final energy of both a D4 empirical dispersion correction and of a semilocal correlation component lead to significant improvements, with DSD-PBEdRPA … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 88 publications
5
30
1
Order By: Relevance
“…52 Generally, inner-shell orbitals were frozen, but in subsets where such orbitals come close enough to the valence shell to qualify as 'honorary valence orbitals', 53 the same frozen-core settings were used as in Refs. 46,54,55 Similar to the unregularized (x)DSD functionals, one fully optimized κ-DSD also has six adjustable linear parameters: cX,HF, cC,DFT, c2ab, c2ss(=c2aa+c2bb), and for the D3(BJ) dispersion correction, one prefactor s6 and one parameter a2 for the damping function (like in refs 56,57 we constrain a1=s8=0). On top of that, our new κ(x)DSD functionals also contain the PT2 regularization parameter κ.…”
Section: Computational Detailsmentioning
confidence: 99%
“…52 Generally, inner-shell orbitals were frozen, but in subsets where such orbitals come close enough to the valence shell to qualify as 'honorary valence orbitals', 53 the same frozen-core settings were used as in Refs. 46,54,55 Similar to the unregularized (x)DSD functionals, one fully optimized κ-DSD also has six adjustable linear parameters: cX,HF, cC,DFT, c2ab, c2ss(=c2aa+c2bb), and for the D3(BJ) dispersion correction, one prefactor s6 and one parameter a2 for the damping function (like in refs 56,57 we constrain a1=s8=0). On top of that, our new κ(x)DSD functionals also contain the PT2 regularization parameter κ.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The large pruned integration grid SG-3 was used across the board. 54 Generally, inner-shell orbitals were frozen, but in subsets where such orbitals come close enough to the valence shell to qualify as “honorary valence orbitals”, 55 the same frozen-core settings were used as in refs ( 48 ), ( 56 ), and ( 57 ).…”
mentioning
confidence: 99%
“…Xu and co-workers ,, used B3LYP orbitals while calculating the final energy for the original XYG3 functional and its later variants lrc-XYG3 and XYGJ-OS . Along this line, xDSD, ωDSD, and ωDSD3 functionals from the Martin group and the combinatorially optimized range-separated double-hybrid ωB97M(2) by Mardirossian and Head-Gordon have shown remarkable performance for extensive and chemically diverse main-group benchmarks such as MGCDB84 (Main-Group Chemistry Database with about 5000 test cases divided into 84 subsets) and GMTKN55 (General Main-group Thermochemistry, Kinetics, and Noncovalent interactions, 55 problem subsets). In a recent study, Zhang and Xu explored the limits of the XYG3-type double hybrids utilizing B3LYP reference orbitals to be consistent with the original XYG3 functional.…”
mentioning
confidence: 99%
“…The LD0110-LD0590 angular integration grid was used throughout, being a pruned Lebedev-type integration grid similar to Grid = UltraFine in Gaussian or SG-3 in Q-Chem . The same frozen core settings were used as in refs and . MP3 calculations in both HF and KS orbitals were performed using Q-Chem 5.4, def2-TZVPP being used throughoutwe previously found that this basis set is adequate for post-MP2 corrections, both in composite WFT and in double-hybrid DFT contexts. , All calculations were performed on the ChemFarm HPC cluster in the Faculty of Chemistry at the Weizmann Institute of Science.…”
mentioning
confidence: 99%
See 1 more Smart Citation